Optimisation of 3D printed concrete for artificial reefs: Biofouling and mechanical analysis. (22nd February 2021) - Ly, Océane; Yoris-Nobile, Adrian I.; Sebaibi, Nassim; Blanco-Fernandez, Elena; Boutouil, Mohamed; Castro-Fresno, Daniel; Hall, Alice E.; Herbert, Roger J.H.; Deboucha, Walid; Reis, Bianca; Franco, João N.; Teresa Borges, Maria; et al.
Highlights: Geopolymer and cement concretes for artificial reefs were prepared using 3D printing. The type of binder in concrete affects its biofouling and durability when immersed in seawater. Biofouling and mechanical properties at medium term are better with cement compared to geopolymer as binders. Cement appears to be the better binder compared with geopolymer for the fabrication of artificial reefs. Abstract: Protection, restoration, and regeneration of aquatic habitats are an increasingly important issue and are requiring intensive research. In the marine environment, artificial reefs may be deployed to help offset habitat loss, increase local biodiversity and stimulate the recovery of ecosystems. This study aimed at the fabrication of artificial reefs by 3D printing. In the framework of the European INTERREG Atlantic Area collaborative project "3DPARE", six printed concrete formulations with limited environmental impact, based on geopolymer or cement CEM III binders and recycled sands, were immersed in the Atlantic along British, French, Portuguese and Spanish coasts. The colonisation of the concrete samples by micro- and macroorganisms and their durability were assessed after 1, 3 and 6 months of immersion. Results showed that both parameters were better with CEM III compared to geopolymer-based formulations. Therefore the use of CEM III should be prioritised over these geopolymer binders in 3D printed concrete for artificial reef applications.